Liquid Chromatography–Mass Spectrometry Study Focusing on Neuroprotective Effect of Compounds Obtained from Bacopa monnieri Juice - Reddy, K. Ramachandra (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: According to Ayurvedic literature, Brahmi is highly recommended for the management of psychiatric problems since it acts on the brain. In traditional Ayurvedic medicine, Brahmi, a herb is recommended for the management of various psychological disorders such as Alakshmi (inauspicious condition), Unmada (insanity), and Apasmara (epilepsy). Drug quality is a basic necessity in this day and age, and analytical testing can help combat impurities or subpar pharmaceuticals. Materials and Methods: Compound analysis of Brahmi Juice ( Swarasa) using liquid chromatographic mass spectrometry (LC-MS). Results: LC-MS analysis shows major compound such as L-Phenylalanine, Phenylacetylene, DL-Arginine, Azelaic acid, Erucamide, D-(+)- Pyroglutamic acid, L-Glutamic acid, Valine, Choline, L-Isoleucine, DL-Tryptophan, L-(-)-Methionine, and Beta-Ionone which play a significant role in neuroprotection. Conclusion: The study showed the presence of compounds rich in neurotransmitters which also act as neurotonics having their specific neuroprotective effect in conditions such as Alzheimer’s Disease, Parkinsonism, and Dementia. By employing a wide array of testing procedures, manufacturers are able to ensure compliance with regulatory requirements and supply consumers with a better product that effectively delivers Brahmi’s therapeutic benefits.